Population projections, the flow of new households and structural housing demand - Adele Bergin; Paul Egan (The Economic and Social Research Institute (ESRI), 2024)
This report provides estimates of structural (demographic) housing demand at a regional level. Any assessment of structural future housing demand relies on assumptions around (1) population growth, (2) headship rates (the typical household size) and (3) rates of obsolescence of the housing stock. Each of these key drivers of structural housing demand is subject to uncertainty, therefore a range of alternative assumptions for each key driver is considered and results from a range of scenarios are presented.
Keywords: 330; Housing market; Demand; Private household; Population development; Scenario technique; Forecast; Ireland; Wohnungsmarkt; Nachfrage; Privater Haushalt; Bevölkerungsentwicklung; Szenariotechnik; Prognose; Irland